2002
DOI: 10.1007/s004280100481
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing polycystic adenosis of parotid gland with dysplasia and ductal carcinoma in situ

Abstract: We describe three cases of sclerosing polycystic adenosis (SPA) of the parotid gland, a salivary condition analogous to fibrocystic disease of the breast. For the first time, immunoreactivity for oestrogen and progesterone receptors was demonstrated, suggesting a possible participation of hormone stimulation in its pathogenesis. In addition, all our cases showed foci of dysplasia of the ductal epithelium, which in one case was severe enough to amount to carcinoma in situ. This feature that has not previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…On the other hand, other studies have demonstrated a monoclonal origin for this lesion, thus corroborating a possible neoplastic origin 2,12) . In addition, because it resembles a fibrocystic lesion, breast adenosis, and different degrees of dysplasia, some authors consider SPA to be a low-grade malignant neoplasm 13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other studies have demonstrated a monoclonal origin for this lesion, thus corroborating a possible neoplastic origin 2,12) . In addition, because it resembles a fibrocystic lesion, breast adenosis, and different degrees of dysplasia, some authors consider SPA to be a low-grade malignant neoplasm 13) .…”
Section: Discussionmentioning
confidence: 99%
“…It may also present ductal epithelial hyperplasia and atypia that may range from mild to severe dysplasia/carcinoma in situ 1,5) . An important characteristic of these lesions occurs due to the presence of acini filled with dispersed zymogen and reddish granules 13) . Immunohistochemistry may be positive for cytokeratin, epithelial membrane antigen, S100 proteins, cystic disease protein fluid, or smooth muscle alpha cells.…”
Section: Discussionmentioning
confidence: 99%
“…Coarse, strongly eosinophilic cytoplasmic granules are often found within acinar structures [1,2]. The features of SPA are similar to fibrocystic changes of the breast and some evidence suggests that cells within SPA exhibit estrogen and progesterone receptor activity [9].…”
Section: Diagnosismentioning
confidence: 90%
“…There are ectatic ducts and cysts with apocrine-like metaplasia and epithelial hyperplasia that may exhibit cribriform growth [1,8]. Atypia may be found within the ductal epithelium to a degree that warrants the diagnosis of dysplasia [9]. Occasional hyaline globules reminiscent of collagenous spherulosis may be present.…”
Section: Diagnosismentioning
confidence: 99%
“…SPA was first described by Smith et al in 1996 in a series of 9 cases [1]. Since then just over 50 cases in a few larger series and several case reports have been published [2][3][4][5][6][7][8][9][10][11][12][13][14]. The most common site is the parotid gland with less frequent occurrence in the submandibular gland and intraoral minor salivary glands.…”
Section: Introductionmentioning
confidence: 99%